Using the Altman Model in Predicting Financial Default in the Saudi Banking Sector: Comparative Study Pre- and Post the Corona Pandemic - Alamoudi, May Abdulaziz; Alharbi, Muruj (Journal of Economic, Administrative and Legal Sciences, 2024)
The study examines the effectiveness of Altman Model in predicting the financial default of the Saudi banking sector before and after the Corona Pandemic (COVID-19). The study is a quantitative study that followed the deductive approach, the financial data was collected from the annual reports of nine banks in Saudi Arabia over the period of 2018 to 2021. The period chosen includes the two years pre and post Corona pandemic, to indicate whether the pandemic had any impact on the financial performance of the Saudi banks. Our results revealed the success of Altman Model in predicting the failure of Saudi banks during the study period. Except for the three (3) banks that defaulted, other banks survived during the Corona pandemic. Hence, the Corona pandemic had little effect on the financial indicators of the banks, providing evidence that the Saudi Banking sector is characterized by strength and durability that made it pass this ordeal without collapsing. Therefore, Altman Model is recommended along with other models for measuring financial default to determine the financial status of companies in way that is more accurate.